Proprotein convertase subtilisin/kexin type 9: a promising marker of cardiovascular risk in post-menopausal diabetic women in primary prevention - Rottura, Michelangelo; Barbieri, Maria Antonietta; Siniscalchi, Carmine; Di Micco, Pierpaolo; Drago, Selene Francesca Anna; Gigliotti De Fazio, Marianna; Cicero, Arrigo Francesco Giuseppe; Fogacci, Federica; Armentaro, Giuseppe; Sciacqua, Angela; Arcoraci, Vincenzo; Irrera, Natasha; et al. (Frontiers in Medicine, 2025)
Background and aimsProprotein convertase subtilisin/kexin type 9 (PCSK9) increases circulating LDL levels and cardiovascular disease (CVD) risk; its levels may be related to the dysregulation of glycemic control and may be affected by estrogens. The aim of this study was to assess factors related to PCSK9 levels, and to evaluate the correlation between PCSK9 levels and CV parameters in post-menopausal diabetic women in primary prevention.MethodsGeneralized linear models (GLM) were adopted to evaluate predictors of PCSK9 levels as well as factors related to CV outcomes, such as pulse wave velocity (PWV), pulse pressure (PP), and augmentation index (AI).ResultsA total of 135 post-menopausal diabetic women, with a median (Q1-Q3) serum PCSK9 levels of 370.3 (344.0–409.4) ng/ml were enrolled. Apolipoprotein B values resulted an independent predictor of PCSK9 levels (B = 1.023; p < 0.001). However, LDL values were inversely related to PCSK9 levels (B = −0.578; p < 0.001). PCSK9 levels influenced PWV (B = 0.010; p = 0.010), but did not influence other CV outcomes.ConclusionApoB and LDL may influence PCSK9 levels and PCSK9 directly influence PWV in post-menopausal diabetic women in primary prevention. Therefore, the relationship between PCSK9 and primary prevention cannot be excluded, thus highlighting its role as biomarker of CV risk.